Toward servitization: Optimal design of uptime‐guarantee maintenance contracts. Issue 10 (15th July 2022) - Hezarkhani, Behzad; Nagarajan, Mahesh; Tong, Chunyang
Abstract: This paper analyzes the contracting of maintenance services provided by an original equipment manufacturer (OEM) to an operator for a device. The service provider can exert different levels of maintenance effort during the course of the contract and the device's reliability (uptime) is influenced by these levels. However, the service provider's effort level is noncontractible. Our research seeks to find the optimal structures, as well as parameters, of performance‐based maintenance contracts. We single out a unique uptime‐guarantee contract structure that contains profit‐maximizing contracts in many situations. Complete servitization is the essence of such optimal contract structures. With this contract structure, the service provider simply guarantees 100% uptime and compensates the operator's for any occurred downtime at a higher unit rate than it charges for maintenance services. Our findings show that some of the well‐known performance‐based contract structures used in practice (e.g., pay‐for‐performance contracts) can be suboptimal for the OEMs. We incorporate the customer's ability to affect the uptime and show that the optimal contract structures can also coordinate the customer's effort. We demonstrate the advantages and limitations of offering menus of contracts to increase the service provider's expected profits. Finally, through simulations using a sample data set, we find that a contract designed using the key ideas in our paper shows very promising results for practitioners.